Fermentation Technology using Phanerochaete chrysosporium to Improve the Quality of Nutrition of Pod Coffe as Ruminant Feed - Engkus Ainul Yakin; Ali Mursyid Wahyu Mulyono; Ahimsa Kandi Sariri (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
This study was carried out to assess the effect of solid state fermentation by using P. chrysosporium on nutrient composition of pod coffee and to evaluate its potency as ruminant feed in vitro. The in vitro experiment was conducted to determine fermentability of treated pod coffee. Fermented pod coffee by P. chrysosporium 0, 1, 2, 3, 4 % (R0 to R4). Pod coffee were air dried to moisture content of 10%-15% and then fermented with P. chrysosporium. The solid state fermentation trials were carried out on a laboratory scale. The result of this studi were fermentation of pod coffee by P. chrysosporium increased protein from 10.36% to 12.64%, and cellulose from 18.51% to 23.80%, and decreased lignin, from 64.42% to 44.04%, tannin from 1.02% to 0.18%, and caffeine from 1.39% to 0.20%. There were no differences in ruminal pH and N-ammonia production but volatile fatty acid production and dry matter digestibility decreased as the fermented of pod coffee level increased. The ruminal protozoa population in fermented of pod coffee diets was lower than the control diets (P<0.05). Conclusion in this study that fermented of pod coffee with P. chrysosporium can increase protein and cellulose concentration, but decrease lignin, tannin, and caffeine concentration.